2000
DOI: 10.1051/aas:2000187
|View full text |Cite
|
Sign up to set email alerts
|

CCD photometry and proper motions of late–type stars in the young open cluster Stock 2

Abstract: Abstract. We present the results of the first CCD BV RI photometric and proper motion study of late-type stars in the young open cluster Stock 2.Twenty-one fields of approximately 5 × 5 size have been observed photometrically, from which we have identified 118 candidate members based on their positions on colour-magnitude diagrams relative to theoretical isochrones. From a comparison of the known star density of the Pleiades, we estimate the contamination of this selection process due to background stars to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Stock 2 is by far the most populous cluster (down to the limiting magnitude of Tycho-2) of our sample. There has been a controversial discussion about the distance modulus and reddening of the cluster (see the overview in the recently published work of Foster et al 2000). Here we just summarise that distance moduli from 7.4 mag (Piskunov 1980) up to 8.36 mag (Pandey et al 1989) are proposed; the reddenings found are of the order of E B−V ≈ 0.3 mag.…”
Section: Stockmentioning
confidence: 84%
“…Stock 2 is by far the most populous cluster (down to the limiting magnitude of Tycho-2) of our sample. There has been a controversial discussion about the distance modulus and reddening of the cluster (see the overview in the recently published work of Foster et al 2000). Here we just summarise that distance moduli from 7.4 mag (Piskunov 1980) up to 8.36 mag (Pandey et al 1989) are proposed; the reddenings found are of the order of E B−V ≈ 0.3 mag.…”
Section: Stockmentioning
confidence: 84%
“…For the cluster NGC 6991 whose (V, B-V) CMD is poorly populated and clearly lacks a well-defined cluster main-sequence, we measured the cluster parameters from Gaia DR2 CMD. Sources of the cluster UBV data include Krzeminski & Serkowski (1967) and Foster et al (2000) for Stock 2, Sung & Bessell (1999;NGC 2168), Prosser et al (1995;NGC 6475), Kharchenko et al (2005;NGC 6991) and Maciejewski et al (2008;NGC 7762). Figure 1 provides (V, B-V) CMDs for all but clusters NGC 6991 and NGC 7762 with the radial velocity and proper motions confirmed members of each cluster highlighted with red filled circles (dwarfs) and squares (giants).…”
Section: Revised Cluster Parametersmentioning
confidence: 99%